On Shannon entropy and its applications - Paulo Saraiva (Kuwait Journal of Science)
A brief and intuitive introduction to Shannon entropy is presented, including some of its properties. The application of this measure is exemplified in two different contexts from what was in its genesis: biological diversity and an original study on student migration.